2003
DOI: 10.1080/0962935031000096935
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of hemodialysis on serum levels of the proinflammatory cytokines

Abstract: Chronic inflammation is a common feature of end-stage renal disease, which carries a heightened risk of atherosclerosis and other co-morbid conditions. Dialysis treatment per se can bring additional risk factors for inflammation, such as increased risk of local graft and fistula infections, impure dialysate or bio-incompatible membranes. Our study was designed to determine whether a hemodialysis session leads to an acute substantial alteration in the plasma levels of the proinflammatory cytokines interleukin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
4
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 21 publications
6
52
4
1
Order By: Relevance
“…These data indicate that the enhanced IL-10 level detected in our ESDR patients might be ascribed to the reduced Th1 cytokine TNF-β and decreased inflammatory cytokine IL-8 shown in them. The experiment conducted by Rysz et al [10] showed that the level of IL-8 was lower in HD patients when compared with healthy controls, and Tarakcioglu and colleagues reported IL-8 level of ESRD patients significantly decreased following HD, [21] results that are consistent with our findings of IL-8 alterations in ESRD patients. It is well-known that IL-8 is an inflammation mediator and chemotactic granulocyte factor.…”
Section: Discussionsupporting
confidence: 83%
“…These data indicate that the enhanced IL-10 level detected in our ESDR patients might be ascribed to the reduced Th1 cytokine TNF-β and decreased inflammatory cytokine IL-8 shown in them. The experiment conducted by Rysz et al [10] showed that the level of IL-8 was lower in HD patients when compared with healthy controls, and Tarakcioglu and colleagues reported IL-8 level of ESRD patients significantly decreased following HD, [21] results that are consistent with our findings of IL-8 alterations in ESRD patients. It is well-known that IL-8 is an inflammation mediator and chemotactic granulocyte factor.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, TNF-α levels were not very high even in the patients with other signs of inflammation, as also reported by others (33,34). It is interesting to note that CRP levels after the change of the water purification system correlated closely with the previous CRP levels, suggesting that the patients present a pattern of inflammatory activity dependent on other factors.…”
Section: Discussionsupporting
confidence: 63%
“…CRP is specifically recognized as a marker of inflammation and atherosclerosis (30), whereas cTnI levels in HD patients are indicative of subclinical myocardial ischemic injury (5,6,31). We found elevated levels of hsCRP in half of the children on HD and a rise in cTnI levels in 25% of this pediatric cohort, and this may be an indicator of early subclinical atheromatous disease in our patients.…”
Section: Discussionmentioning
confidence: 70%
“…It is also becoming increasingly apparent that HD in itself confers a risk, but the pathophysiologic mechanisms remain elusive. In adults, there is evidence from isotopic (2), electrocardiographic (3,4), biochemical (5,6), and echocardiographic (7,8) studies implicating HD as a source of recurrent subclinical myocardial cell injury, even in the absence of preexisting large-vessel epicardial coronary artery disease (CAD). Using single photon emission computed tomography, we demonstrated acute reductions in global and segmental myocardial blood flow during HD, with matched reversible reductions in segmental contractile function (2), consistent with the definition of myocardial stunning (9).…”
mentioning
confidence: 99%